Astrocyte‐dependent protective effect of quetiapine on GABAergic neuron is associated with the prevention of anxiety‐like behaviors in aging mice after long‐term treatment. (18th June 2014) - Wang, Junhui; Zhu, Shenghua; Wang, Hongxing; He, Jue; Zhang, Yanbo; Adilijiang, Abulimiti; Zhang, Handi; Hartle, Kelly; Guo, Huining; Kong, Jiming; Huang, Qingjun; Li, Xin‐Min
Abstract Previous studies have demonstrated that quetiapine (QTP) may have neuroprotective properties; however, the underlying mechanisms have not been fully elucidated. In this study, we identified a novel mechanism by which QTP increased the synthesis of ATP in astrocytes and protected GABAergic neurons from aging‐induced death. In 12‐month‐old mice, QTP significantly improved cell number of GABAegic neurons in the cortex and ameliorated anxiety‐like behaviors compared to control group. Complimentary in vitro studies showed that QTP had no direct effect on the survival of aging GABAergic neurons in culture. Astrocyte‐conditioned medium (ACM) pretreated with QTP (ACMQTP) for 24 h effectively protected GABAergic neurons against aging‐induced spontaneous cell death. It was also found that QTP boosted the synthesis of ATP from cultured astrocytes after 24 h of treatment, which might be responsible for the protective effects on neurons. Consistent with the above findings, a Rhodamine 123 test showed that ACMQTP, not QTP itself, was able to prevent the decrease in mitochondrial membrane potential in the aging neurons. For the first time, our study has provided evidence that astrocytes may be the conduit through which QTP is able to exert its neuroprotective effects on GABAergic neurons. <boxed-text content-type="graphic" id="jnc12771-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> The neuroprotective properties of quetiapine (QTP) have not been fully understood. Here, we identify a novel mechanism by which QTP increases the synthesis of ATP in astrocytes and protects GABAergic neurons from aging‐induced death in a primary cell culture model. In 12‐month‐old mice, QTP significantly improves cell number of GABAegic neurons and ameliorates anxiety‐like behaviors. Our study indicates that astrocytes may be the conduit through which QTP exerts its neuroprotective effects on GABAergic neurons.